Relationship between the sense of nursing professional pride and adversity quotient, grit levels among nurses in blood purification centers: a multicenter cross-sectional study - Xu, Wenbin; Li, Lin; Jiang, Qian; Fang, Yiqian; Yang, Qian (Frontiers in Psychology, 2024)
Objective: This study aims to examine nursing professional pride levels in blood purification center nurses, explore its relationship with adversity quotient and grit, and identify influencing factors.Using convenience sampling, this study selected 231 nurses from blood purification centers at 11 tertiary hospitals in China during July to August 2023 as research subjects. A general data survey questionnaire, nurse professional pride scale, nurse adversity quotient self-assessment scale, and the Oviedo resilience scale were employed for the investigation. The results were statistically analyzed using descriptive analysis, t-tests, one-way ANOVA, Pearson correlation analysis, and multiple stepwise linear regression analysis.In the blood purification center, the average scores were as follows: nursing professional pride (69.53±15.21), adversity quotient (132.90±41.10), and grit (30.95±10.54). There was a significant positive correlation between nursing professional pride, adversity quotient, and grit (P<0.001). Multiple linear regression analysis (n=231) revealed that education background, professional title, average monthly income, adversity quotient, and grit significantly influenced nursing professional pride (P<0.001). The R 2 value indicates that this study accounted for 76.2% of the total variance in nursing professional pride.The findings of this study indicate that blood purification center nurses have a moderate level of nursing professional pride. The level of nursing professional pride can be enhanced by focusing on factors such as adversity quotient and grit.Registration ： This study was approved by the Ethics Committee of Pidu District People's Hospital, Chengdu, China (2021 No. 231). All participants were informed of the relevant information and research purposes before their participation. Participants were also required to independently and anonymously complete the questionnaires.